Homemade Glove Port for Single-Incision Pediatric Endosurgery (SIPES) Appendectomy—How We Do It - Martynov, Illya; Lacher, Martin (European Journal of Pediatric Surgery Reports, 2018)
Introduction Single-incision pediatric endosurgery (SIPES) for the treatment of acute appendicitis in children has recently gained popularity due to its advantages including minimization of postoperative scars or less incisional pain. The principal disadvantages of SIPES include the limited degrees of freedom of movement and high health care costs. To overcome these issues, some surgeons have reported to use noncommercial ports for SIPES appendectomy.Case Report In this report, we present a case of a 10-year-old female patient with acute appendicitis undergoing SIPES appendectomy using own homemade glove port and straight rigid instruments.Conclusion SIPES appendectomy using the glove port is a low-cost alternative to commercially available port systems. It is easy to set up and use.
Keywords: children; glove port; appendicitis; single-incision pediatric endosurgery